Does melatonin alleviate ototoxic effect caused by administration of cisplatin? (Annals of Medical Research, 2021)
Aim: In this study, it was aimed to experimentally investigate the protective effects of melatonin in the cisplatin-induced ototoxicity.Material and Methods: Ten Wistar-albino rats were included in the study. Two equal groups were generated randomly as cisplatin and melatonin groups. Rats’ underwent Auditory Brainstem Response (ABR) and Distortion Product Otoacoustic Emission (DPOAE) testing before the drug administration and the results were recorded. Both tests were repeated 72 hours after the cisplatin administration in all rats.Results: Significant difference was found between the I-IV interval values before the treatment and after the treatment both in cisplatin and melatonin group. As well as the significant difference in hearing threshold value changes, statistically, significant differences in ABR-I and ABR-IV interval variations were also seen between the cisplatin and melatonin groups. A statistically significant decrease was found between the initial and final control SNR (signal-to-noise ratio) levels within the cisplatin group in the evaluations at 2000Hz, 3000Hz and 4000Hz. Statistically, significant differences were observed between SNR levels when the melatonin group was compared with the cisplatin group. Conclusion: Melatonin appears to reduce cisplatin-induced ototoxicity in rats. Although, the use of supplementary therapies targeting to reduce the toxic effects in clinical studies is still a controversial point.
Keywords: Melatonin; cisplatin; ototoxicity; DPOAE; ABR.